An audit of innovation drivers: some empirical findings in Greek agri-food firms. Issue 2 (27th November 2018) - Kafetzopoulos, Dimitrios; Skalkos, Dimitris
Abstract : Purpose: The purpose of this paper is to develop a conceptual model and examine the relevance of a set of five dynamic drivers to building and sustaining the innovation capability of agri-food firms. Design/methodology/approach: The empirical data were acquired through a recent study of 436 Greek agri-food firms. Regression analysis was employed to examine the correlation between innovation drivers and each of the four innovation capability dimensions, namely, product innovation, process innovation, organizational innovation and marketing innovation. Findings: The findings verify that quality orientation and process management are the two most important innovation drivers. However, the impact of learning orientation, collaborations and environmental dynamism on a firm's agri-food innovation capability is yet to be investigated. Research limitations/implications: This study has not investigated how firms' characteristics form the drivers and barriers to innovation at the company. Moreover, a second limitation is related to the kind of innovation that drivers boost. This research does not separate between radical and incremental innovation. Practical implications: In order to maintain their sustainable development and enhance their whole innovation capability, agri-food firms should closely relate their innovation capability dimensions to the formulation of a strategy and harmonization of innovation and innovation drivers' activities. Originality/value: The main contribution of this paper is that it develops an appropriate research framework (a proposed structural model) for examining the links among the five innovation drivers with each of the four innovation capability dimensions.